Factors causing construction waste: a case study in Aceh Besar Regency / Hafnidar A. Rani ... [ et al.] - A. Rani, Hafnidar; Syammaun, Tamalkhani; Darwis, Darwis; Mubarak, Muhammad Hafidz; Aqsha, Muhammad Shafly (Universiti Teknologi MARA, Perak, 2024)
Construction waste poses significant losses in terms of material, time, and finances, stemming from various direct and indirect activities. To address this issue effectively, it is imperative to identify the root causes of construction waste. This study aims to ascertain the factors contributing to construction waste and determine the most dominant causes thereof. The research problem revolves around identifying the factors causing construction waste and pinpointing the primary contributors to this issue. The study seeks to shed light on the factors influencing construction waste, with a particular focus on the Santriwati Dayah Darul Muttaqin Dormitory Development Project in Aceh Besar Regency. The factors examined in this research include waiting time, materials, human resources, construction implementation, management, design and documentation, residuals, and external factors. The analytical methods employed comprise correlation analysis, multiple regression analysis, and descriptive analysis. The findings of the descriptive analysis revealed that construction waste primarily arises from issues related to materials, construction implementation, and management in the aforementioned project. Among these factors, management emerged as the most dominant. This study provides valuable insights into the factors influencing construction waste in Aceh Besar Regency, contributing to the development of targeted strategies for waste reduction and improved project efficiency.